Potential of non-flat solar sail for higher characteristic acceleration - Santos Lula Barros, Letícia; Hiraki, Koju; Assis da Silveira, Marcelo; Chak, Yew Chung; Abdullah, Amirul Fiqri; Varatharajoo, Renuganth (Elsevier, 2025)
Solar sails offer a promising means of propelling spacecraft by harnessing Solar Radiation Pressure. Although non-flat solar sails have traditionally been considered less efficient in generating thrust, altering the sails’ design to a non-flat configuration can enhance structural stability, allowing for thinner sail films and reducing overall mass. Consequently, non-flat sails could enable the use of larger sails for future space exploration without excessive mass. This study comprehensively explores non-flat solar sails using three folding techniques: Miura-Ori, Iso-area flasher by Palmer-Shafer, and Parachute-folded. The main goal is to optimize the characteristic acceleration while maintaining its structural integrity. Using Finite Element Analysis (FEA), we analyze deformation patterns and thrust generation to identify the most effective folding technique for a non-flat solar sail. The Parachute-folded sail with five support points demonstrated significantly improved the characteristic acceleration while maintaining a lower deformation than the other two folded configurations and the flat sail counterpart. Further, an enhancement was achieved by strategically integrating a polyimide reinforcement layer along its outer borders, resulting in a sail model with a higher structural resistance to deformation and decreased moment reaction compared to the uniform thickness Parachute-folded sail. Due to computational limitations, the thickness evaluated for this analysis was made in the interval of 30 μm to 400 μm. Investigating new solar sail designs can make large sails more feasible for future missions that are capable of shorter transfer times.